Concentration-discharge relationships of dissolved rhenium in alpine catchments reveal its use as a tracer of oxidative weathering - Hilton, RG; Turowski, JM; Winnick, M; Dellinger, M; Schleppi, P; Williams, KH; Lawrence, CR; Maher, K; West, M; Hayton, A (American Geophysical Union, 2021)
Oxidative weathering of sedimentary rocks plays an important role in the global carbon cycle. Rhenium (Re) has been proposed as a tracer of rock organic carbon (OCpetro) oxidation. However, the sources of Re and its mobilization by hydrological processes remain poorly constrained. Here, we examine dissolved Re as a function of water discharge, using samples collected from three alpine catchments that drain sedimentary rocks in Switzerland (Erlenbach and Vogelbach) and Colorado, USA (East River). The Swiss catchments reveal a higher dissolved Re flux in the catchment with higher erosion rates, but have similar [Re]/[Na+] and [Re]/[SO42−] ratios, which indicate a dominance of Re from OCpetro. Despite differences in rock type and hydro-climatic setting, the three catchments have a positive correlation between river water [Re]/[Na+] and [Re]/[SO42−] and water discharge. We propose that this reflects preferential routing of Re from a near-surface, oxidative weathering zone. The observations support the use of Re as a proxy to trace rock-organic carbon oxidation, and suggest it may be a hydrological tracer of vadose zone processes. We apply the Re proxy and estimate CO2 release by OCpetro oxidation of 5.7 +6.6/−2.0 tC km−2 yr−1 for the Erlenbach. The overall weathering intensity was ∼40%, meaning that the corresponding export of unweathered OCpetro in river sediments is large, and the findings call for more measurements of OCpetro oxidation in mountains and rivers as they cross floodplains.